CONDITIONS, THE DRIVING FACTOR, AND MARKETING RESIDENTIAL INVESTMENT SECTOR IN THE CITY OF SEMARANG - Rio Sri Whisnu Sjahputra; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2018)
The demand of housing in Semarang is increasing each year. This certainly is an investment opportunity for investor, especially developer.  In the investment of real estate industrial, it is required the analysis. Investment, marketing, and other driving factors affecting the housing investment in Semarang. This is a qualitative descriptive research, with primary and secondary data collection technique, interviewing and collecting data that are available. The primary resources consist of three people; one person as the organizer the housing investment in Semarang, and the other two as the industrial practitioners of housing investment. Result shows, the housing investment in Semarang is effected by house demand and bargain, bureaucracy and legitimacy in practicing the investment, price application offered by developer, supporting facility, and developer marketing. The high demand of housing is the main reason of property investment in Semarang. One of the elements of permission legitimacy that must be fulfilled by developer is the quantity, and duration of the authorization. However, the government has simplified and shortened the authorization duration. The infrastructure in Semarang needs to be upgraded to raise the housing investment. Further, the field analysis, housing development must be based on decree of ministry. Balanced house, in which 1 : 2 : 3, with facility and attraction as the edge. Another point is the marketing, which the consumers in Semarang in general are end user, not speculative user. Thus, the marketing strategy mostly uses consumer gathering, exhibiting, and advertising in varied media. Based on above results, it is suggested that the government in Semarang to develop better infrastructure in the future. The developer also can use this investment opportunity, because it promises the investment development.